Clinical Relevance of Pre-Existing and Treatment-Induced Anti-Poly(Ethylene Glycol) Antibodies - Freire Haddad, Helena; Burke, Jacqueline A.; Scott, Evan A.; Ameer, Guillermo A. (Regenerative engineering and translational medicine, 2022)
Poly(ethylene glycol) (PEG) is a nontoxic, hydrophilic polymer that is often covalently attached to proteins, drugs, tissues, or materials; a procedure commonly referred to as PEGylation. PEGylation improves solubility, circulation time, and reduces immunogenicity of therapeutic molecules. Currently, there are 21 PEGylated drugs approved by the Food and Drug Administration (FDA), and more in the developmental stage. In addition to the polymer’s applications in the clinic, PEG is widely used as a solvent and emulsifying agent in the formulation of cosmetics, cleaning, and personal care products. Due to the ubiquitous presence of the polymer in everyday products, patients can develop antibodies against PEG (αPEG Abs) that can be problematic when a PEGylated drug is administered. These αPEG Abs can provoke hypersensitivity reactions, accelerated drug clearance, and decreased therapeutic efficacy. Herein, we review how the prevalence of PEG in everyday products has induced αPEG Abs within the general public as well as the effect of these Abs on the performance of PEGylated therapeutics. We will focus on clinical manifestations following the administration of PEGylated drugs. Lay Summary Poly(ethylene glycol) (PEG) is a polymer found in products including cosmetics, personal care products, cleaning agents, medicine, and food. Due to the prevalence of PEG, people can develop antibodies (αPEG Abs) against the polymer, which recognize PEG as foreign. Of note, PEG is frequently incorporated into drug formulations to improve therapeutic efficacy. Complications can arise when a patient receiving a PEGylated drug has previously developed αPEG Abs from interactions with PEG in everyday products. The presence of high concentrations of αPEG Abs in blood can result in decreased treatment efficacy and allergic reactions to a wide range of therapeutics.